Sistem Pencatatan Keuangan Yang Efektif Bagi UMKM Seblak (Seblak Samyang) - Adilah Khalisah Putri; Jivia Oktapiani; Resty Made Pertiwi; Serly Chantika; Helmi Herawati (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
Seblak MSMEs have an important role in the Indonesian economy, but often face difficulties in recording their finances. This research aims to develop an effective financial recording system for Seblak MSMEs. The method used is a direct approach and interviews. The results show that implementing a recording system based on SAK EMKM can increase the transparency and accuracy of financial reports, help make better decisions, and support business sustainability.This article aims to provide guidance on how an effective financial recording system can be implemented by Seblak MSMEs. By implementing a daily cash book, structured bookkeeping, using accounting applications, separating personal and business finances, as well as wise cash flow management, business owners can manage finances more transparently and measurably. By keeping proper financial records, seblak business owners can improve business planning, optimize profits, and avoid financial problems that can hinder business development.